Pengembangan Agribisnis Berbasis Komoditas Unggulan di Kabupaten Sumenep - Fatmawati Fatmawati; Dody Tri Kurniawan; Mohammad Anwar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Sumenep Regency has a wealth of agribusiness superior commodities such as rice, corn, chili, onions, tobacco, coconut, and the livestock sector in the form of cattle and goats. This research aims to explore this potential and formulate an adaptive and sustainable agribusiness development strategy. The approach used involves field studies, primary and secondary data collection, and SWOT analysis. The results of the study show that obstacles such as low access to technology, inadequate infrastructure, and weak farmer institutions need to be answered with strategies to strengthen institutions, modernize technology, develop derivative products, and digitize the market. The implementation of this strategy is projected to be able to increase the productivity and welfare of farmers, as well as encourage sustainable regional economic growth.